2015
DOI: 10.1177/2150137815573790
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Trauma-Focused Cognitive Behavioral Therapy for Treating PTSD and Co-occurring Depression Among Children and Adolescents

Abstract: We evaluated the effectiveness of trauma-focused cognitive behavioral therapy (TF-CBT) for treating posttraumatic stress disorder and co-occurring depression symptoms across 21 betweengroup studies representing the data of 1,860 children and adolescents (1,106 girls and 754 boys). Separate meta-analytic procedures were conducted for studies that implemented wait-list/no treatment and alternative treatment comparisons to estimate aggregated treatment effect of TF-CBT and moderators of effect size magnitude. Lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 43 publications
(43 reference statements)
4
51
0
1
Order By: Relevance
“…In addition, along with the PTSD symptom reduction, also symptoms of depression, general anxiety, and dissociation were reduced significantly, even though these were not directly addressed in the treatment. The amelioration of comorbid depressive symptoms we observed is consistent with the findings of a meta‐analysis evaluating the effectiveness of TFT on symptoms of PTSD and comorbid depression in children and adolescents (Lenz & Hollenbaugh, ), which showed TFT to be more effective in reducing depressive symptoms than other (nontrauma‐focused) treatments. Lastly, our data are also in line with studies in adult PTSD populations that consistently found that secondary symptoms decreased along with the PTSD symptoms with exposure‐based treatments (Van Minnen, Zoellner, Harned, & Mills, ).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, along with the PTSD symptom reduction, also symptoms of depression, general anxiety, and dissociation were reduced significantly, even though these were not directly addressed in the treatment. The amelioration of comorbid depressive symptoms we observed is consistent with the findings of a meta‐analysis evaluating the effectiveness of TFT on symptoms of PTSD and comorbid depression in children and adolescents (Lenz & Hollenbaugh, ), which showed TFT to be more effective in reducing depressive symptoms than other (nontrauma‐focused) treatments. Lastly, our data are also in line with studies in adult PTSD populations that consistently found that secondary symptoms decreased along with the PTSD symptoms with exposure‐based treatments (Van Minnen, Zoellner, Harned, & Mills, ).…”
Section: Discussionsupporting
confidence: 88%
“…There are many adaptions of CBTs that have been tailored to address negative reactions to childhood trauma, maltreatment, and early life adversity. A meta-analysis of trauma-focused CBTs (TF-CBT) found large effect sizes for TF-CBT relative to no treatment, and small-tomoderate improvements over other alternative therapies (e.g., supportive therapy, family therapy, child-centered play therapy) (Lenz & Hollenbaugh, 2015). Similarly, in a meta-analysis of child and adolescent survivors of natural and man-made disasters, CBTs showed improvements in posttraumatic reactions with large effect sizes (Newman, Pfefferbaum, Kirlic, Tett, Nelson, & Liles, 2014).…”
Section: Cognitive Behavioral Therapiesmentioning
confidence: 99%
“…There may be an inability to remember aspects of the trauma, difficulty in experiencing positive emotions, extreme negative emotions or emotional numbing, and extremely negative beliefs about the self, others, and the dangerousness of the world in general. Meta-analyses and narrative reviews show that family-based, traumafocused cognitive behaviour therapy is the systemic intervention for PTSD in young people with the strongest evidence base (Dorsey et al, 2017;Kowalik et al, 2011;Lenz and Hollenbaugh, 2015). This family-based intervention was described earlier in the section on child sexual abuse.…”
Section: Disorders Where Anxiety Is a Central Featurementioning
confidence: 99%